2017
DOI: 10.1039/c7ra00134g
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free rutile and anatase TiO2nanocrystals as electron extraction layers for high performance inverted polymer solar cells

Abstract: Ligand-free rutile and anatase TiO2nanocrystals were synthesizedviaa hydrolytic sol–gel method. The improved power conversion efficiency was achieved by using anatase TiO2nanocrystals as electron extraction layer in the organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(89 citation statements)
references
References 53 publications
14
64
0
Order By: Relevance
“…For all samples, two main characteristic peaks with a symmetric feature are located at binding energies of 458.5‐459.1 eV and 464.3‐465.0 eV corresponding to Ti 2p 3/2 and Ti 2p 1/2 , respectively. Peaks’ positions and energy difference of about 5.8‐6.0 eV between Ti 2p doublet are in good agreement with the energy values reported for Ti 4+ in TiO 2 . As annealing temperature increased, the peaks’ position slightly shifted to a lower value of binding energy and FWHM of the Ti 2p peaks decreased.…”
Section: Resultssupporting
confidence: 87%
“…For all samples, two main characteristic peaks with a symmetric feature are located at binding energies of 458.5‐459.1 eV and 464.3‐465.0 eV corresponding to Ti 2p 3/2 and Ti 2p 1/2 , respectively. Peaks’ positions and energy difference of about 5.8‐6.0 eV between Ti 2p doublet are in good agreement with the energy values reported for Ti 4+ in TiO 2 . As annealing temperature increased, the peaks’ position slightly shifted to a lower value of binding energy and FWHM of the Ti 2p peaks decreased.…”
Section: Resultssupporting
confidence: 87%
“…The UV absorption peak related to the bandgap of crystalline TiO 2 H was observed in shorter wavelengths as compared to the bandgap peak of amorphous TiO 2 in the ternary SiO 2 /TiO 2 /Pt systems (Figure c). It has been previously reported that amorphous TiO 2 has lower bandgaps and lower energy levels CB than crystalline TiO 2 . The energy level of crystalline TiO 2 CB is, therefore, higher than that of amorphous TiO 2 and ZnO, where the electrons excited in ZnO were not able of a transfer to crystalline TiO 2 CB due to larger Schottky barriers at the ZnO/TiO 2 interface.…”
Section: Resultsmentioning
confidence: 92%
“…The X‐ray diffractogram of the as‐deposited Pt on a glass substrate presents cubic crystal structure with the lattice planes shown by Miller index of ( hkl ), whereas the as‐deposited TiO 2 did not show any peak corresponding to a crystalline phase, indicating its amorphous structure. Thermal annealing at 500 °C transformed the amorphous TiO 2 to a mixture of crystalline structures of rutile and brookite phases (TiO 2 H) . The half‐width of the XRD peaks of the deposited Pt increased after the heat treatment indicating an increase in the size of the crystals.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand‐free anatase TiO 2 NPs and amorphous TiO 2 were synthesized according to the method earlier reported in the literature . The anatase TiO 2 nanocrystals were synthesized by mixing 1 mL aqueous solutions of TiCl 3 (20%) and 1 mL HCl (6 m ) with 60 mL ethanol and heating the resultant reaction mixture at 75 °C for 6 h in a water bath.…”
Section: Methodsmentioning
confidence: 99%